Transport Equation with Boundary Conditions Related to the Interior Solution. Issue 2 (23rd February 2017) - Boulanouar, Mohamed
ABSTRACT: This work deals with the transport equation endowed with a new form of boundary conditions. These boundary conditions relate the input flux to the total flux by means a boundary operator. Thanks to the boundedness of this operator, we prove that the transport equation is governed by a strongly continuous semigroup. We end this work by two applications.